(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: colo-duodenal fistula; malignant; clinical suspicion DOI: 10.3329/jcmcta.v20i2.5629 Journal of Chittagong Medical College Teachers’ Association 2009: 20(2):53-55